2022
DOI: 10.3389/fmicb.2022.889618
|View full text |Cite
|
Sign up to set email alerts
|

Methane Reduction Potential of Brown Seaweeds and Their Influence on Nutrient Degradation and Microbiota Composition in a Rumen Simulation Technique

Abstract: This study aimed to investigate the effects of two brown Icelandic seaweed samples (Ascophyllum nodosum and Fucus vesiculosus) on in vitro methane production, nutrient degradation, and microbiota composition. A total mixed ration (TMR) was incubated alone as control or together with each seaweed at two inclusion levels (2.5 and 5.0% on a dry matter basis) in a long-term rumen simulation technique (Rusitec) experiment. The incubation period lasted 14 days, with 7 days of adaptation and sampling. The methane con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Chemical analysis of the seaweeds examined in this work indicated that only A. taxiformis contained measurable amounts of bromoform, explaining the negligible impact that the other two algae had on methanogenesis. Although P. mollis or M. japonica did not reduce methane levels, some seaweeds without anti-methanogenic activity have proven to be potent modulators of rumen microbiomes both in vivo ( Zhou et al, 2018 ) and in a RUSITEC system ( Belanche et al, 2016 ; Zhou et al, 2018 ; Künzel et al, 2022 ) due to the wide range of bioactives present in algae. To our knowledge M. japonica has not previously been evaluated for its effect on microbial communities, while P. mollis has been found to modify the composition of the gut microbial community in mice ( Mendez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analysis of the seaweeds examined in this work indicated that only A. taxiformis contained measurable amounts of bromoform, explaining the negligible impact that the other two algae had on methanogenesis. Although P. mollis or M. japonica did not reduce methane levels, some seaweeds without anti-methanogenic activity have proven to be potent modulators of rumen microbiomes both in vivo ( Zhou et al, 2018 ) and in a RUSITEC system ( Belanche et al, 2016 ; Zhou et al, 2018 ; Künzel et al, 2022 ) due to the wide range of bioactives present in algae. To our knowledge M. japonica has not previously been evaluated for its effect on microbial communities, while P. mollis has been found to modify the composition of the gut microbial community in mice ( Mendez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is some support for this theory in a recent study in which two species of brown seaweeds, A. nodosum and Fucus vesiculosus, were included with the basal diet at a level of 5%. Reductions in CH 4 by 8.9 and 3.6%, respectively, were associated with reductions in total gas production, IVDMD, and the production of VFA [48]. This could imply that the brown seaweeds tested in the current study might not have a direct effect on methanogenic archaea when compared with some other feed additives that are well known for their anti-methanogenic potential, such as A. taxiformis [49], 3-nitrooxypropanol (Bovaer ® ) [50], and a garlic-citrus extract (Mootral Ruminant ® ) [51].…”
Section: Discussionmentioning
confidence: 93%
“…In another study, a reduction of 17% in CH 4 (ml/g dig. OM) was reported on the incorporation of brown seaweed at 5.0% in the diet ( Künzel et al, 2022 ). The reduction in CH 4 production with the inclusion of BW was consistent with the previous reports, where brown seaweeds were used at the almost similar levels.…”
Section: Discussionmentioning
confidence: 99%